Retinal and Brain Organoids: Bridging the Gap Between in vivo Physiology and in vitro Micro-Physiology for the Study of Alzheimer’s Diseases - Brighi, Carlo; Cordella, Federica; Chiriatti, Luigi; Soloperto, Alessandro; Di Angelantonio, Silvia (Frontiers in Neuroscience, 2020)
Recent progress in tissue engineering has led to increasingly complex approaches to investigate human neurodegenerative diseases in vitro, such as Alzheimer’s disease, aiming to provide more functional and physiological models for the study of their pathogenesis, and possibly the identification of novel diagnostic biomarkers and therapeutic targets. Induced pluripotent stem cell-derived cortical and retinal organoids represent a novel class of in vitro three-dimensional models capable to recapitulate with a high similarity the structure and the complexity of the native brain and retinal tissues, thus providing a framework for better mimicking in a dish the patient’s disease features. This review aims to discuss progress made over the years in the field of in vitro three-dimensional cell culture systems, and the benefits and disadvantages related to a possible application of organoids for the study of neurodegeneration associated with Alzheimer’s disease, providing a promising breakthrough toward a personalized medicine approach and the reduction in the use of humanized animal models.